How Gender, Region, And Lifestyle Effect The Decision to Islamic Financial Literacy of Millennial Generation in Greater Jakarta - Kaban, Reny Fitriana; Purnawarman, Dhia Aulia (Indikator: Jurnal Ilmiah Manajemen dan Bisnis, 2024)
The purpose of this research was to analyze how the effect of gender, region, and lifestyle towards Islamic financial of the Millennial generation in Greater Jakarta. The data in this research were obtained by distributing questionnaires with using 100 samples of Millennial generation and used purposive sampling technique. The analytical technique used descriptive analysis and binary logistic test with SPSS version 20 as the tool. Based on the results, the gender and region do not affect the Islamic financial literacy of Millennial generation in Greater Jakarta it means a person's intelligence and ability to manage their personal finances is not determined by gender or by the region in which they live. While the lifestyle affects the Islamic financial literacy of Millennial generation in Greater Jakarta. This means that Millennial generation who have a good lifestyle are also good at managing their finances and are familiar with financial products. Millennials are reminded of the importance of financial literacy in life. Because a person's level of financial literacy will also affect the continuity of that person's economy. The level of financial literacy is also one of the important aspects in making financial decisions. This research has specifically categorized the gender, region, and lifestyle of the Millennial generation's financial Islamic literacy with specific method.